Exact nature of Frenkel – Kontorova dislocations in (2+1) dimensional crystals. (December 2020) - Senjudarvannan, R; Sudha, D; Sasikumar, N P; Priyadharsini, R
Abstract: In this paper, a ground-breaking method have accomplished on widespread Frenkel - Kontorova model which allocates contemplation of dislocations. Here the innovative exact solitary wave resolutions have been inspected on Frenkel-Kontorova model. The configuration of these families of solutions is show the power, capability, fruitfulness and effectiveness of this new-fangled method. These new-fangled solutions have countless solicitations in the field of physics and other subdivisions of physical science. Acquired outcomes will assist as a very imperative landmark in the knowledge of crystal physics. We also have revealed that the generalized Kudrayashov method is an operative contrivance for large class of schemes of Frenkel - Kontorova model.